Pengaruh Ketersediaan SDM Dan Fasilitas Kerja Terhadap Kinerja Pegawai Pada Kantor Dinas Pemadam Kebakaran (DAMKAR) Kota Sorong - Rosalina Tomasoa; Susana Magdalena Welly Muskita; Sesilia Ronga Kaka (JURNAL RISET MANAJEMEN (JURMA), 2023)
This research was conducted to determine the effect of the availability of human resources and work facilities on the performance of firefighters at the Sorong Fire Department. The data used are primary data collected through observation and distribution of questionnaires. To measure these variables, multiple linear regression and the coefficient of determination are used with the help of the IBM SPSS 23 computer application program. Based on the results of the study, it is shown that from the results of the T test, the Sig value for the effect of variable X1 (availability of human resources) on Y (employee performance) is 0.006 <0.05 so it can be concluded that there is no effect of X1 on Y. The Sig value for the effect of variable X2 (work facilities) on Y (Employee Performance) is 0.001 > 0.05 so it can be concluded that there is no effect of X1 on Y. and the results of f test count of 39.749 with a significance level 0.000. The probability is much smaller than the significance level of 0.05 or 5%, so that H0 is accepted. So, it can be concluded that there is no simultaneous influence (together) between the influence of the availability of human resources and work facilities on employee performance at the Sorong City Fire Department (DAMKAR).